(x-2)*(2x-3)=1

Simple and best practice solution for (x-2)*(2x-3)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)*(2x-3)=1 equation:


Simplifying
(x + -2)(2x + -3) = 1

Reorder the terms:
(-2 + x)(2x + -3) = 1

Reorder the terms:
(-2 + x)(-3 + 2x) = 1

Multiply (-2 + x) * (-3 + 2x)
(-2(-3 + 2x) + x(-3 + 2x)) = 1
((-3 * -2 + 2x * -2) + x(-3 + 2x)) = 1
((6 + -4x) + x(-3 + 2x)) = 1
(6 + -4x + (-3 * x + 2x * x)) = 1
(6 + -4x + (-3x + 2x2)) = 1

Combine like terms: -4x + -3x = -7x
(6 + -7x + 2x2) = 1

Solving
6 + -7x + 2x2 = 1

Solving for variable 'x'.

Reorder the terms:
6 + -1 + -7x + 2x2 = 1 + -1

Combine like terms: 6 + -1 = 5
5 + -7x + 2x2 = 1 + -1

Combine like terms: 1 + -1 = 0
5 + -7x + 2x2 = 0

Factor a trinomial.
(1 + -1x)(5 + -2x) = 0

Subproblem 1

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Subproblem 2

Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5

Solution

x = {1, 2.5}

See similar equations:

| 3a+3a+3a= | | -3=3x+9 | | (-1)*(2x+3)=1 | | 4g+4(-6+4g)=1-g | | 3x-3x+12=8 | | 8-3x=3-2x | | 9x+5x=5x+7 | | 4g+3(-8+3g)=1*g | | 8x+12x=120 | | -7x=3x+30 | | 125=r*2.5 | | 22=2l+6 | | z^5-7z^3+5z-1=0 | | x^2-2x=1.1 | | 2+a+4=-1 | | 6n+3=5+6n-2 | | 6x+6=-15 | | x^2-2x-1.1=0 | | -32-5x=4x+12 | | -3-4x=-9 | | 3x^2+15x+12= | | 7y+14=21x | | 10x-126=14x+35 | | -14-7x=-3 | | -5.5=-0.02x^2+x+0.5 | | -5.5=-0.02x+x+0.5 | | 5(n+7)=-44+2(n+6) | | y=-0.02x^2+x+0.5 | | 2x+7-3x=1 | | y=-0.02x+x+0.5 | | 3x+27=10x-33 | | -40=33x+15 |

Equations solver categories